Characterizing Non-Industrial Private Forest Landowners' Forest Management Engagement and Advice Sources. Issue 2 (1st February 2019) - Crowley, Morgan A.; Hartter, Joel; Congalton, Russell G.; Hamilton, Lawrence C.; Christoffersen, Nils D.
Abstract: Non-industrial private forestland (NIPF) owners have options for engagement by following management strategies that reduce wildfire risk on their forestlands. Forest management engagement is a broad term with underlying categories and management implications. To better understand these categories, we examine interview data on the engagement of forest landowners from a case study of private forestland owner perspectives in northeast Oregon, USA. NIPF landowners outline two types of forest management engagement, one for property and one for community-focused forestland management. NIPF owners describe actions for engagement in public forestland management and how these actions differ from engagement in private management. Additionally, NIPF owners establish barriers to engagement in both public and private forestland management. Our findings can be used to better identify unengaged private forestland owners in the U.S. West, informing the design and implementation of extension and outreach for NIPF owners.